Genetic Predisposition to Low-Density Lipoprotein Cholesterol May Increase Risks of Both Individual and Familial Alzheimer's Disease - Tan, Jiang-Shan; Hu, Meng-Jin; Yang, Yan-Min; Yang, Yue-Jin (Frontiers in Medicine, 2022)
Background: Previous observational studies have provided conflicting results on the association between low-density lipoprotein cholesterol (LDL-C) level and the risk of Alzheimer’s disease (AD). Objective: We used a two-sample Mendelian randomization (MR) study to explore the causal associations between LDL-C level and the risks of individual, paternal, maternal, and family history of AD. Methods: Summary-level genetic data for LDL-C were acquired from results of the UK Biobank GWAS. Corresponding data for paternal, maternal, and family history of AD were obtained from the NHGRI-EBI Catalog of human genome-wide association studies, while data for individual AD were obtained from the MR-Base platform. A Two-sample MR study was performed to explore the causal association between LDL-C level and the risks of individual, paternal, maternal, and family history of AD. Results: Genetically predicted LDL-C was positively associated with individual [Odds ratio (OR) = 1.509, 95% confidence interval (CI) = 1.140–1.999; P=4.0×10-3], paternal [OR = 1.109, 95% CI = 1.053–1.168; P=9.5×10-5], maternal [OR = 1.132, 95% CI = 1.070–1.199; P=2.0×10-5], and family history of AD [OR = 1.124, 95% CI = 1.070–1.181; P=3.7×10-6] in inverse variance weighted analysis. After performing weighted median and MR-Egger analysis, consistent results were observed. There was no horizontal pleiotropy in the two-sample MR analysis. Conclusions: High level of LDL-C may increase risks of both individual and familial AD. Decreasing the LDL-C to a reasonable level may help to reduce the related risk.